Atherosclerosis and Oxidant Stress: A New Perspective - Holtzman, Jordan L.; Holtzman, Jordan L. (Springer US : Imprint: Springer, 2008)
Vascular injury is initiated by oxidant injury to the vessel wall. This volume is organized around the role of oxidant damage in this disease process and provides a collection of the most recent studies, representing various disciplines, that can serve as the basis for further improvements in our understanding and control of cardiovascular and cerebral vascular disease. Jordan L. Holtzman, M.D., Ph.D. is Professor, Departments of Pharmacology and Medicine and Division of Environmental Health Sciences, University of Minnesota, Minneapolis, Minnesota.